2009
DOI: 10.1103/physrevlett.103.184501
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propelled Dropwise Condensate on Superhydrophobic Surfaces

Abstract: In conventional dropwise condensation on a hydrophobic surface, the condensate drops must be removed by external forces for continuous operation. This Letter reports continuous dropwise condensation spontaneously occurring on a superhydrophobic surface without any external forces. The spontaneous drop removal results from the surface energy released upon drop coalescence, which leads to a surprising out-of-plane jumping motion of the coalesced drops at a speed as high as 1 m=s. The jumping follows an inertial-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

35
1,165
11
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,134 publications
(1,214 citation statements)
references
References 34 publications
35
1,165
11
3
Order By: Relevance
“…Boreyko and Chen [55] of a self-jumping droplet by assuming that the surface energy (E s ), released via the coalescence of condensate microdrops, is fully converted into kinetic energy (E k ). However, the experimental velocities of the self-jumped microdrops are apparently smaller than their theoretical values.…”
Section: Cmdsp Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Boreyko and Chen [55] of a self-jumping droplet by assuming that the surface energy (E s ), released via the coalescence of condensate microdrops, is fully converted into kinetic energy (E k ). However, the experimental velocities of the self-jumped microdrops are apparently smaller than their theoretical values.…”
Section: Cmdsp Mechanismmentioning
confidence: 99%
“…Different from traditional superhydrophobic surfaces, which are characterized by the bouncing or rolling off of deposited millimeter-size large drops, [32,33] CMDSP surfaces support the self-removal capability of smallscale condensate microdrops. It has been reported that classical superhydrophobic lotus leaves (Figure 1a), [34][35][36][37] as well as artificial surfaces consisting of hierarchical micro-and nanostructures, [38] one-tier microstructures, [39][40][41][42][43] or nanostructures [44,45] with larger characteristic interspaces, present a low-adhesivity property to the deposited water macrodrops, but become highly adhesive to condensed microdrops (Figure 1b). This is because moisture easily penetrates the microscale valleys or cavities.…”
mentioning
confidence: 99%
“…Coalescence-induced jumping phenomena occur on superhydrophobic surfaces but within a small range of initial droplet radii. Recent interest in these phenomena has led to the influence of the droplets radii on the resulting jumping velocity to be explored [3,[8][9][10][11][12]. However, previous analysis on coalescence-induced jumping droplets focused only a limited range of contact angles and droplet radius [10][11][12].…”
mentioning
confidence: 99%
“…[36] This departure size is in close agreement with previous experimental observations and theoretical predictions. [37][38][39] From the set of hierarchical surfaces investigated ( Figure S3), droplets departed most frequently from the surface with an edge-to-edge pillar spacing of ~20 m.…”
mentioning
confidence: 99%